Treatment of encephalopathy during fulminant hepatic failure by haemodialysis with high permeability membrane. Issue 9 (September 1978) - Denis, J; Opolon, P; Nusinovici, V; Granger, A; Darnis, F
Abstract : Forty-one patients with fulminant hepatic failure and coma underwent 180 periods of haemodialysis with polyacrylonitrile membrane (AN 69 HD). Hepatic failure was due to viral hepatitis in 40 and drugs in one. Total recovery of consciousness occurred in 17 patients (43.6%), and partial in seven (17.9%)--that is, an overall figure of 61.5%. Regain of consciousness was not related to liver regeneration as assessed by levels of factor V and hepatocyte volume fraction. At the time of the first haemodialysis, neurological status was significantly impaired in the patients who could not be aroused. Mean duration of coma grade IV averaged 6.1 +/- 4.3 days and mean duration of illness until death or decerebration 8.6 +/- 8.3 days. Of the 17 patients who totally regained consciousness, nine recovered and eight died (three from intercurrent complications and five with no liver regeneration).